Development of an electronic controller for lettuce production in greenhouses - Marques Filho, Aldir Carpes [UNESP]; Rodrigues, Jean Paulo; Sartorio de Medeiros, Simone Daniela; Rodrigues de Medeiros, Sergio Ricardo (Univ Estadual Mato Grosso Sul, 2020)
The objective of this study was to develop an electronic controller for microclimate control in greenhouses, as well as to verify if the automated control system affects the productivity of two varieties of lettuce Lactuca sativa. The control system was developed based on the Atmega 2560 and compatible transducers. An experimental field analysis was carried out over a production cycle for two lettuce varieties. The experimental results showed that the designed equipment worked according to the implemented programming algorithm. However, the ventilation, nebulization and shading actuators did not control environmental variables, due to under sizing. The irrigation process was correctly controlled throughout the experimental period. The electronic controller promoted increase in the productivity of lettuce varieties. There was increase of 28% in total fresh weight; 10% in stem diameter; 7 and 8% in height gain and average diameter, respectively.
Keywords: Arduino; lettuce; plant physiology; micro-controllers